Traditional and complementary medicines in the management of type 2 diabetes mellitus: a narrative review / Izzah Zahra Nasrudin and Nur Wahida Zulkifli - Nasrudin, Izzah Zahra; Zulkifli, Nur Wahida (Faculty of Pharmacy, 2024)
Many individuals with diabetes often explore traditional and complementary medicines (TCM) as an alternative, believing in their perceived minimal side effects and enhanced effectiveness compared to conventional treatments for diabetes mellitus. This review aims to conduct a narrative review of TCM approaches for managing type 2 diabetes mellitus, focusing on diabetic parameters such as glycemic, lipid profiles, weight, and blood pressure. We searched PubMed and ScienceDirect using terms such as "traditional and complementary medicine," "type 2 diabetes mellitus," "diabetes mellitus," "management," and "herbal" over a period of 5 years (2017–2021). The screened articles were based on predefined inclusion and exclusion criteria, which were then validated and extracted. We included a total of 47 articles that met the criteria in this review and categorized them according to diabetic parameters (adapted from CPG Management of T2DM, 2020). The majority of herbal supplements (e.g., ginger, American ginseng, herbal mixtures), health supplements (e.g., Gingko biloba, zinc, vitamin D), dietary supplements (e.g., wheat germ and camel milk), and practices (e.g., acupuncture and homeopathy) exhibited positive effects, improving diabetic parameters towards their intended targets. This review can serve as a valuable reference for healthcare professionals involved in the management of this condition.